Effect of interval training on the factors influencing maximal oxygen consumption: a systematic review and meta-analysis - Rosenblat, M. A.; Granata, C.; Thomas, S. G. (Sports Medicine, 2022)
Background: The maximal rate of oxygen consumption (VO2max) is an important measure in exercise science as it is an indicator of cardiorespiratory fitness. Individual studies have identified central and peripheral adaptions to interval training that may underlie improvements in VO2max, but there is no compilation of results. Objective: We aimed to systematically review the adaptive responses to high-intensity interval training (HIIT) and sprint interval training (SIT) on the central and peripheral factors influencing VO2max in healthy individuals. Data Sources: SPORTDiscus and MEDLINE (up to and including 13 June, 2020) were explored to conduct the literature search. Study Selection: Reviewed studies met the following criteria: (1) were in the English language; (2) prospective in nature; (3) included at least three interval sessions or were at least 1 week in duration; (4) contained HIIT or SIT; (5) involved participants between the ages of 18 and 65 years; and (6) included at least one of the following central (blood volume, plasma volume, hemoglobin mass, left ventricular mass, maximal stroke volume, maximal cardiac output) or peripheral factors (capillary density, maximal citrate synthase activity, mitochondrial respiration associated with VO2max). Results: Thirty-two studies (369 participants, 49 were female) were included in the quantitative analyses, consisting of both HIIT (n = 18) and SIT (n = 17) interventions. There were only statistically significant changes in hematological measures (plasma volume) following HIIT. There was a significant increase in left ventricular mass following HIIT (7.4%, p < 0.001) and SIT (5.3%, p = 0.007) in inactive individuals, though the change following SIT may be misleading. There was only a significant increase in maximal stroke volume (14.1%, p = 0.015) and maximal cardiac output (12.6%, p = 0.002) following HIIT. In addition to central factors, there was a significant increase in capillary density (13.8%, p < 0.001) following SIT in active individuals. With respect to maximal citrate synthase activity, there were improvements following HIIT (20.8%, p < 0.001) and SIT (15.7%, p < 0.001, I2 = 97%) in active individuals. The results for mitochondrial respiration suggested that there was no statistically significant improvement following HIIT (5.0%, p = 0.585). Conclusions: Improvements in the central and peripheral factors influencing VO2max were dependent on the interval type. Only HIIT led to a statistically significant improvement in cardiac function. Both HIIT and SIT increased maximal citrate synthase activity, while changes in other peripheral measures (capillary density, mitochondrial respiration) only occurred with SIT.